2023
DOI: 10.1111/pbi.14071
|View full text |Cite
|
Sign up to set email alerts
|

The RUBY reporter enables efficient haploid identification in maize and tomato

Abstract: Summary In vivo haploid induction has been extended from maize to monocotyledonous plants like rice, wheat, millet and dicotyledonous plants such as tomato, rapeseed, tobacco and cabbage. Accurate identification of haploids is a crucial step of doubled haploid technology, where a useful identification marker is very pivotal. R1‐nj is an extensively used visual marker for haploid identification in maize. RFP and eGFP have been shown to be feasible in identifying haploid. However, these methods are either limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…(2022) recently developed an efficient and accurate (99.1% accuracy) haploid selection marker through co-expression of two transcription factor genes ( ZmC1 and ZmR2 ) in novel haploid inducer line called ‘Maize Anthocyanin Gene InduCer 1 (MAGIC1)’. Shortly after, Wang et al. (2023) showed that expression of RUBY enabled 100% accuracy of haploid identification based on deep betalain pigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) recently developed an efficient and accurate (99.1% accuracy) haploid selection marker through co-expression of two transcription factor genes ( ZmC1 and ZmR2 ) in novel haploid inducer line called ‘Maize Anthocyanin Gene InduCer 1 (MAGIC1)’. Shortly after, Wang et al. (2023) showed that expression of RUBY enabled 100% accuracy of haploid identification based on deep betalain pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chen et al (2022) recently developed an efficient and accurate (99.1% accuracy) haploid selection marker through co-expression of two transcription factor genes (ZmC1 and ZmR2) in novel haploid inducer line called 'Maize Anthocyanin Gene InduCer 1 (MAGIC1)'. Shortly after, Wang et al (2023) showed that expression of RUBY enabled 100% accuracy of haploid identification based on deep betalain pigmentation. The development of a group of inducers with numerous anthocyanin markers and HIRs above 12.0% allowed for effective haploid generation and screening (Rotarenco et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The upgraded version, MAGIC2, could identify haploids from diploids due to differential anthocyanin accumulation in immature embryos, coleoptiles, sheaths, roots, leaves, and dry seeds. Instead of anthocyanin synthesis pathway for haploid selection, Wang et al (2023) utilized the RUBY reporter, a betalain biosynthesis system, as a new biomarker. The expression of RUBY resulted in deep betalain pigmentation in maize embryos as early as 10 DAP and enabled 100% accuracy of immature haploid embryo identification.…”
Section: H Vs D Determination Advantages Limitationsmentioning
confidence: 99%
“…Importantly, a fast technique for visual screening of wheat haploids was developed by combining the haploid inducer generated by editing TaMTL and embryo-specific anthocyanin markers, providing a promising strategy for a large-scale haploid inducer in different crops [151]. Recently, a RUBY reporter system, a background-independent and efficient marker for haploid identification, has been established, which enables easy and accurate haploid identification in maize and tomato, which will be promising in double haploid breeding in different crops [152].…”
Section: Facilitating Double Haploid Breeding Technologymentioning
confidence: 99%